2004
DOI: 10.1021/jm030317k
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a New Class of Anilinoquinazoline Inhibitors with High Affinity and Specificity for the Tyrosine Kinase Domain of c-Src

Abstract: Deregulated activity of the nonreceptor tyrosine kinase c-Src is believed to result in signal transduction, cytoskeletal and adhesion changes, ultimately promoting a tumor-invasive phenotype. We report here the discovery of a new class of anilinoquinazoline inhibitors with high affinity and specificity for the tyrosine kinase domain of the c-Src enzyme. Special attention was directed toward finding inhibitors selective against KDR tyrosine kinase in order to ensure that the in vivo profile of a specific Src in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(65 citation statements)
references
References 43 publications
2
62
1
Order By: Relevance
“…KX2-329, a biaryl-based, non-ATPcompetitive Src inhibitor, and also a tubulin polymerization inhibitor, significantly reduced threshold shifts at 24 h, one week and four weeks after the noise exposure, and also reduced noiseinduced OHC loss. KX2-328, an ATP-competitive Src inhibitor [53], was not effective in reducing NIHL. Overall, the data indicated that the biaryl-based, non-ATP-competitive Src inhibitor KX2-329 was capable of significantly reducing NIHL when present in the cochlea.…”
Section: Src Ptk Inhibitors To Prevent Nihlmentioning
confidence: 91%
“…KX2-329, a biaryl-based, non-ATPcompetitive Src inhibitor, and also a tubulin polymerization inhibitor, significantly reduced threshold shifts at 24 h, one week and four weeks after the noise exposure, and also reduced noiseinduced OHC loss. KX2-328, an ATP-competitive Src inhibitor [53], was not effective in reducing NIHL. Overall, the data indicated that the biaryl-based, non-ATP-competitive Src inhibitor KX2-329 was capable of significantly reducing NIHL when present in the cochlea.…”
Section: Src Ptk Inhibitors To Prevent Nihlmentioning
confidence: 91%
“…Similarly, higher contents of Cl in drinking water may create problems in throat and digestive system along with imparting saline taste and corrosion [23]. Alkalinity is also an important parameter of water quality but its concentration beyond certain limit causes many problems like hardness, kidney stone, gas trouble, damage of metallic pipes and severe irritation of skin, eyes and mucous membrane [24]. High level of Na is associated with an increase in blood pressure in children, male and female of all ages [25].…”
Section: Minerals Assessmentmentioning
confidence: 99%
“…Three main Src family members are present in the epidermis (Src, Fyn and Yes), and initially, we looked at the effect of either homozygous deletion of fyn or yes in Redundancy within the Src family members is known; however, it was not possible to address this genetically due to problems with the viability of the double and triple mutants. Therefore, we used the small molecule kinase inhibitor AZD0530 that inhibits all Src family kinases (30). Prior treatment of animals with AZD0530 resulted in a significant attenuation of the ability of TPA to initiate division of the LRCs ( Figure 2C).…”
Section: Src Kinase Activity Is Required For Lrc Mobilizationmentioning
confidence: 99%